Evaluation of Antimony Tri-Iodide Crystals for Radiation Detectors - Toshiyuki Onodera; Koei Baba; Keitaro Hitomi (Science and Technology of Nuclear Installations)
This study was carried out to examine the potential of antimony tri-iodide (SbI3) as a material for radiation detectors that operate at room temperature. SbI3 is a compound semiconductor with an AsI3-type crystal structure, high atomic number (Sb: 51, I: 53), high density (4.92 g/cm3), and a wide band-gap energy (2.2 eV). In addition, crystalline SbI3 is easy to grow by conventional crystal growth techniques from melting phase because the material exhibits a low melting point (171°C) and undergoes no phase transition in the range of its solid phase. In this study, SbI3 crystals were grown by the Bridgman method after synthesis of SbI3 from 99.9999% pure Sb and 99.999% pure I2. The grown crystals consisted of several large grains with red color and were confirmed to be single-phase crystals by X-ray diffraction analysis. SbI3 detectors with a simple planar structure were fabricated using the cleavage plates of the grown crystals, and the pulse-height spectra were recorded at room temperature using an 241Am alpha-particle (5.48 MeV) source. The detector showed response to the alpha-particle radiation.